2021
DOI: 10.1038/s41598-021-83374-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of palmitoylation on the dimer formation of the human dopamine transporter

Abstract: The human dopamine transporter (hDAT) is one in three members of the monoamine transporter family (MAT). hDAT is essential for regulating the dopamine concentration in the synaptic cleft through dopamine reuptake into the presynaptic neuron; thereby controlling hDAT dopamine signaling. Dysfunction of the transporter is linked to several psychiatric disorders. hDAT and the other MATs have been shown to form oligomers in the plasma membrane, but only limited data exists on which dimeric and higher order oligomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Among the five possible conserved Cys residues in rodents (r) and human (h), each (rDAT: 6,135,341,522,580;hDAT: 6,135,342,523 and 581) are exposed for palmitoylation, and mutational studies indicate 60% reduction in incorporation at the Cys580 (rDAT) site (Rastedt et al, 2017). Furthermore, Cys581 palmitoylation of hDAT leads to formation of stable and energetically favorable hDAT dimers with functional effects on DA uptake (Zeppelin et al, 2021). Various studies found that DAT palmitoylation increases the DA uptake Vmax and reduces the likelihood of degradation whereas depalmitoylation enhances DA efflux, decreases DA uptake Vmax, and increases the occurrence of lysosomal-associated degradation similar to the effects of phosphorylation (Khoshbouei et al, 2004;Moritz et al, 2015;Wang C. et al, 2016).…”
Section: Palmitoylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the five possible conserved Cys residues in rodents (r) and human (h), each (rDAT: 6,135,341,522,580;hDAT: 6,135,342,523 and 581) are exposed for palmitoylation, and mutational studies indicate 60% reduction in incorporation at the Cys580 (rDAT) site (Rastedt et al, 2017). Furthermore, Cys581 palmitoylation of hDAT leads to formation of stable and energetically favorable hDAT dimers with functional effects on DA uptake (Zeppelin et al, 2021). Various studies found that DAT palmitoylation increases the DA uptake Vmax and reduces the likelihood of degradation whereas depalmitoylation enhances DA efflux, decreases DA uptake Vmax, and increases the occurrence of lysosomal-associated degradation similar to the effects of phosphorylation (Khoshbouei et al, 2004;Moritz et al, 2015;Wang C. et al, 2016).…”
Section: Palmitoylationmentioning
confidence: 99%
“…Palmitoylation on TM12 has a favorable impact on oligomerization but the functional consequences on DAT are unclear (Zeppelin et al, 2021). Many attempts to understand the conformational dynamics of DAT oligomers and to predict distinct oligomeric interfaces have been made using MD simulations (Gur et al, 2017;Jayaraman et al, 2018;Zeppelin et al, 2021). Coarsegrained MD simulations of hDAT show that TM9, TM11, and/or TM12 provide the dimeric interface for oligomerization (Zeppelin et al, 2021).…”
Section: Dat Oligomerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…1,12 As such, recent work has focused on elucidating the molecular mechanisms of post-translation modifications and its effect on human SLC6 transporters. 1,2 These studies include phosphorylation, 13−17 palmitoylation, 18,19 glycosylation, 20−24 and ubiquitination 25 and its implications on transporter dynamics, stability, oligomerization, trafficking, and uptake activity. The glycosylation of SLC6 transporters has been widely documented to affect transporter activity; 20−24 however, various mechanisms of how glycosylation mediates transporter function have been proposed for different SLC6 members.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,12 As such, recent work has focused on elucidating the molecular mechanisms of post-translation modifications and its effect on human SLC6 transporters. 1,2 These studies include phosphorylation, [13][14][15][16][17] palmitoylation, 18,19 glycosylation, [20][21][22][23][24] and ubiquitination 25 and its implications on transporter dynamics, stability, oligomerization, trafficking, and uptake activity.…”
Section: Introductionmentioning
confidence: 99%